A Checklist of the Aspidogastrea (Platyhelminthes: Trematoda) of the World - Alves, Philippe V.; Vieira, Fabiano M.; Santos, Cláudia P.; Scholz, Tomáš; Luque, José L. (Zootaxa, 2015)
A checklist of records of aspidogastrean trematodes (Aspidogastrea) is provided on the basis of a comprehensive survey of the literature since 1826, when the first aspidogastrean species was reported, until December 2014. We list 61 species representing 13 genera within 4 families and 2 orders of aspidogastreans associated with 298 species of invertebrate and vertebrate hosts. The majority of records include bivalves (44% of the total number of host-parasite associations), whereas records from bony fishes represent 32% of host-parasite associations. The aspidogastreans have worldwide distribution, with the highest number of records in the Neartic Region for freshwater hosts and the North Atlantic Ocean for marine ones. The checklist includes a parasite-host list with data on host habitat, site of infection and distribution area of parasites, and a host-parasite list. A limited number of molecular studies on aspidogastreans does not allow us to unravel phylogenetic relationships within the Aspidogastrea.